AB0463 Cutanoeous vasculitis associated to severe infection: study of 27 patients. (23rd January 2014) - Loricera, J.; Calvo-Río, V.; Ortiz-Sanjuán, F.; Fernández-Llaca, H.; González-López, M. A.; González-Vela, M. C.; Mata, C.; Rueda-Gotor, J.; Álvarez, L.; González-Lamuño, D.; Martínez-Taboada, V. M.; González-Gay, M.Á.; et al.
Abstract : Background: Cutaneous vasculitis (CV) can be a clinical manifestation of a severe infection. In such cases a delayed diagnosis or the use of immunosuppressive therapy may impair the prognosis. Objectives: Our objective was to determine the frequency, subtypes of major infections and clinical characteristics of CV associated to severe infections. Methods: Study of a large series of 817 unselected patients with CV seen in the same hospital. A CV was considered as secondary to infection when it was associated to a severe infection and antibiotics were needed for the resolution of the vasculitis. The diagnosis of CV required histological confirmation. Results: In 27 (22 men/5 women) (mean age±SD; 52.5±17.6 years) of 817 patients (3.3%) the CV was associated to a major underlying infection: pneumonia (8 cases), endocarditis (6 cases), meningitis (4 cases), abdominal infection (3 cases), septic arthritis (2 cases), septicemia (2 cases), septic bursitis (1 case), and 1 urinary tract infection (1 case). In all cases, the vasculitic skin lesions were observed at the beginning of the clinical syndrome. The types of skin lesions were palpable purpura (26 patients) and erythematous lesions (1 case). The most common location was the lower limbs. The mean duration of skin lesions was 15±6.9 days. In addition to the specific clinical manifestation of each infection, other clinical manifestations were fever (21 patients) and constitutional syndrome (5 patients). There was not severe visceral vasculitic involvement in any case. Laboratory findings showed, leukocytosis (27 patients), elevated ESR (18 patients), anemia (16 cases), mild hematuria (8 cases), positive rheumatoid factor (6 patients), positive ANA (5 patients), decreased C3 (2 patients), and circulating cryoglobulins (3 cases). None of the 27 patients developed a connective tissue disease in the follow-up. All the patients were treated with antibiotics, and 7 required the use of low-dose corticosteroids for the resolution of the skin lesions. There was a significant delay in the diagnosis of 2 patients with endocarditis of 32 and 45 days, respectively. Two patients died due to complications of the infection, the remaining, recovered completely. Conclusions: Although uncommon, CV may be a clinical manifestation of a serious infection. In this case it may be a red flag that may help the clinician to set up an early diagnosis and treatment of a severe infection. Acknowledgements: This study was supported by grants from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Program, RD08/0075 (RIER) from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None Declared